2016
DOI: 10.1634/theoncologist.2015-0420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Everolimus in Extrapancreatic Neuroendocrine Tumor: A Comprehensive Review of Literature

Abstract: Background. Everolimus, an oral mTOR (mammalian target of rapamycin) inhibitor, is currently approved for the treatment of progressive pancreatic neuroendocrine tumors (NETs). Although promising, only scattered data, often from nondedicated studies, are available for extrapancreatic NETs. Patients and Methods. Asystematicreviewofthepublisheddata was performed concerning the use of everolimus in extrapancreatic NET, with the aim of summarizing the current knowledge on its efficacy and tolerability. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The safety profile of CC-223 appears to be comparable with the previously characterized class of approved mTOR inhibitors [3, 1719], notwithstanding the increased incidence and severity of certain TRAEs. However, toxicity generally emerged early into treatment and was well-managed either by aggressive dose adjustments or standard treatment interventions.…”
Section: Discussionmentioning
confidence: 67%
“…The safety profile of CC-223 appears to be comparable with the previously characterized class of approved mTOR inhibitors [3, 1719], notwithstanding the increased incidence and severity of certain TRAEs. However, toxicity generally emerged early into treatment and was well-managed either by aggressive dose adjustments or standard treatment interventions.…”
Section: Discussionmentioning
confidence: 67%
“…Currently, based on the results of several clinical trials, everolimus (a pharmacologically active inhibitors of mTOR) is approved for the treatment of advanced pancreatic, gastrointestinal and lung NETs (22,23). Moreover, everolimus should be considered a valid therapeutic option for extrapancreatic NETs (24). However, one-third of NET patients show primary insensitivity (primary resistance) to treatment with everolimus, while in others the disease is initially stabilized and then develops resistance (acquired resistance) and disease progression; this could depend on the genetic instability and the heterogeneity of tumor cells (25).…”
Section: Introductionmentioning
confidence: 99%
“…An increased tumor grade [ 42 , 172 , 179 , 223 ], presence of a poorly-differentiated tumor [ 175 ] and an increasing Ki-67 index [ 173 ] are reported to correlate with worse outcomes with SSA treatment ( Table 2 , Right Panel). Some studies reported that a Ki-67 threshold of 5% was more predictive of PFS with SSA treatment than the cut-off value proposed by 2010 WHO classification to separate G1 and G2 (i.e., <3%) [ 172 , 224 ]. SSA therapy is less effective in patients with bone and peritoneal metastases [ 173 ], as well as with any liver metastases [ 42 ] or a high hepatic tumor load [ 173 , 174 , 177 , 179 , 225 ], suggesting its limited role in advanced panNEN patients with aggressive tumors.…”
Section: Predictive Factors For Response To Ssa In Advanced Pannensmentioning
confidence: 99%